2004
DOI: 10.1007/s00253-003-1412-6
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of microbial community generating electricity using a fuel-cell-type electrochemical cell

Abstract: A fuel cell was used to enrich a microbial consortium generating electricity, using organic wastewater as the fuel. Within 30 days of enrichment the maximum current of 0.2 mA was generated with a resistance of 1 kOhms. Current generation was coupled to a fall in chemical oxygen demand from over 1,700 mg l(-1) down to 50 mg l(-1). Denaturing gradient gel electrophoresis showed a different microbial population in the enriched electrode from that in the sludge used as the inoculum. Electron microscopic observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(165 citation statements)
references
References 33 publications
5
154
4
2
Order By: Relevance
“…Although 16S rDNA sequences belonging to the Firmicutes have previously been detected in the anode communities of active fuel cells (Lee et al, 2003;Kim et al, 2004Kim et al, , 2006Rabaey et al, 2004Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007), there are a limited number of publications where Firmicutes represent a dominant portion (450%) of the anode community composition (Rabaey et al, 2004(Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007). Previous studies of MFCs inoculated with Firmicutes isolates only produced current in the presence of an exogenous electron shuttle (Rabaey et al, 2005(Rabaey et al, , 2007Milliken and May, 2007;Pham et al, 2008) or as a byproduct of glucose fermentation (Park, 2001;Kim et al, 2005).…”
Section: Thermophilic Microbial Fuel Cells Kc Wrighton Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Although 16S rDNA sequences belonging to the Firmicutes have previously been detected in the anode communities of active fuel cells (Lee et al, 2003;Kim et al, 2004Kim et al, , 2006Rabaey et al, 2004Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007), there are a limited number of publications where Firmicutes represent a dominant portion (450%) of the anode community composition (Rabaey et al, 2004(Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007). Previous studies of MFCs inoculated with Firmicutes isolates only produced current in the presence of an exogenous electron shuttle (Rabaey et al, 2005(Rabaey et al, , 2007Milliken and May, 2007;Pham et al, 2008) or as a byproduct of glucose fermentation (Park, 2001;Kim et al, 2005).…”
Section: Thermophilic Microbial Fuel Cells Kc Wrighton Et Almentioning
confidence: 99%
“…This is further supported by culture-independent studies, which indicate that the phylogenetic diversity of MFC microbial communities far exceeds that of electrochemically active isolates. Unfortunately, these community studies (Bond et al, 2002;Lee et al, 2003;Holmes et al, 2004;Kim et al, 2004;Rabaey et al, 2004;Aelterman et al, 2006;Jong et al, 2006;Kim et al, 2006) were hampered by the use of lowresolution DNA fingerprinting techniques targeting the 16S ribosomal RNA gene (16S rDNA), the presence of which does not necessarily demonstrate electrochemical activity but may simply be an artifact of gene persistence in the environment (Manefield et al, 2002). Furthermore, because these studies focused on gene presence (16S rDNA) rather than gene expression (16S rRNA) they could not elucidate active members of the anode biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, several methods have been explored to investigate biofilm form, size, and structure, ranging from traditional colony forming unit (CFU) counting to super‐resolution fluorescent imaging techniques 41, 42, 43. However, these methods described so far are either invasive or do not allow assessment of global morphological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [12] studied bacterial community structure (BCS), compartmentalization and activity in a MFC for a long period (18 months) and reported that BCS varied significantly in the anode biofilm. The research group as well showed that within 30 days of enrichment of microbial community was generated electricity (0.2 mA), using organic wastewater as the fuel [13]. Recently, Zhang, Zhu, Li, Liao and Ye [14] reported that biofilm is a crucial component in MFC for electrogenesis and it required only 14 days to be completely grown up at the anode compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [12] have proposed that these microbial clumps consist of bacteria that ferment the complex fuel into simple fermentation products. These products can then be used as substrate for electrochemically active bacteria within the biofilm to generate electricity [13,28].…”
Section: Performance Of Mfc With Pomementioning
confidence: 99%